PEMANTAATAN KOTORAN TERNAK SAPI SEBAGAI ENERGI ALTERNATTT NruUIH LINGKUNGAN DIKANAGARIAN GURUN PANJANG KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Ihsan, Wirdatul - (STKIP PGRI Sumbar, 2014)
This research was conducted in the Kenagarian Gurun Panjang Kecamatan BayangKabupaten Pesisir Selatan, which aims to examine the use of cow dung as an environmentallyfriendly alternative energy source in terms of: (1) Potential Raw Materials, (2) Availability ofHuman Resources (HR), (3) the role of organizations or groups, and (4) availability or cost ofcapital, which is located on di Kenagarian Gurun Panjang Kecamatan Bayang Kabupaten PesisirSelatan. This study used a descriptive method of cow dung in the Kenagarian Gurun PanjangKecamatan Bayang Kabupaten Pesisir Selatan. Descriptive Technique is a study of the incidenceof moderate or already happening. The population in this study were all heads of family farmerscollecting data through observation / direct observation of spaciousness and pacificationquestionnaire, a sample of 35 heads of households in the study breeder. The data analysisperformed in this study by analyzing the percentage of utilization of cow dung as anenvironmentally friendly alternative energy. The study found: (1) Judging from the aspect of rawmaterial which is owned, Kenagarian Gurun Panjang has the potential to support the use of cowdung as an environmentally friendly alternative energy. (2) An examination of the humanresources do not support the use of cow dung as an environmentally friendly alternative energy.(3) While looking at the organization or group does not support the use of cow dung as anenvironmentally friendly alternative energy. (4) availability or cost of capital, the main capital isvery supportive but in terms of the cost of manufacture do not support the use of cow dung as anenvironmentally friendly alternative energy in Kenagarian Gurun Panjang Kecamatan BayangKabupaten Pesisir Selatan.